PENGEMBANGAN EKONOMI KREATIF BERBASIS DESA DALAM PERSPEKTIF MAQASHID SYARIAH - Masruroh, Nikmatul; Suprianik, Suprianik (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This research aims, first; identify creative economic models based on local wisdom in the village; second; examine creative models that exist in the village from the perspective of maqashid shariah. This objective is carried out with a qualitative approach, the type of research used is a case study with data collection techniques of observation, interviews and documentation. The analysis used is interpretive and descriptive analysis by analyzing the validity of the data using technique and source triangulation. The results of these studies are first; in the some villages, a developing creative economy has several models, namely product creativity models, social media models, service models and industrial models. Second, these models when studied from the perspective of maqashid sharia can fulfill the aspects of hifdz annafs, hifdz al aql, hifdz al mal. However, in terms of the sustainability of the human dimension, it has not been able to increase public literacy about the importance of the human role in the development process, especially through the creative economy. The creative economy is not considered as a support for development, but according to the maqashid sharia perspective it can contribute to household economic growth